Pengaruh Pendidikan Kesehatan Tentang Pemberian Asi Pada Ibu Antepartum Terhadap Inisiasi Menyusu Dini Di Ruang Bersalin RSUD Bayu Asih Purwakarta - Reni Rohimah; Rika Susanti (Pusat Riset dan Inovasi Nasional, 2021)
Mother’s breastfeeding coverage in Indonesia is still low at just 42% below the WHO target. Factors contributing are the mother's knowledge, the role of health workers, and working mothers. Those data is reinforced by the fact in the hospital, where there are many mothers who formula feed their babies on the first day of birth. The situation was caused by the mother during ante partum not get antenatal care properly. So that health education efforts to provide information about breastfeeding needs to be. Method of this research. Quasi experiment design with non randomized pretest-posttest control group without has used in this research. Samples are 10 maternal ante partum latent phase in the delivery room with specific inclusion criteria. Data collection methods. the type of questionnaires which were completed and returned by respondents. the form of a questionnaire. Data analysis was using the t test. Results showed effect of health education on breastfeeding to the implementation of the IMD, with difference in mean pre-posttest was 2,900, SD = 1,663 and p value = 0.000 (a< 0,005). Suggestion. Improving health promotion in the delivery room.